Analisis Pengelolaan Sampah di Lingkungan RW 05 pada Masyarakat Desa Gunung Bunder 1 - Yusi Srihartini; Rio Kartika; Ami Primarni; Abdul Haris; Evinovita Evinovita; Rosihan Anwar Dani; Debi Milanda; Puti Andini; Ayi Apriani; Putri Pebriani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Waste management in Gunung Bunder 1 RW 05 Village, Pamijahan District, Bogor Regency remains a major issue due to low public awareness and limited waste management infrastructure. This condition leads to waste accumulation around households and rivers, which affects both public health and environmental quality. This study aims to increase community awareness and participation in waste management while strengthening collaboration between residents, local authorities, and university students.The method involved field observation, interviews with RT/RW administrators and community leaders, as well as community service programs such as 3R (Reduce, Reuse, Recycle) education, community clean-up activities, the “Clean Friday” program, and the installation of anti- littering banners in key locations. The results showed increased awareness and participation among residents, a reduction in indiscriminate waste disposal, and stronger collaboration between students and the community. This program is expected to foster a sustainable environmental care culture in Gunung Bunder 1 RW 05.